Survey on rail transit mobile edge computing network security - Renchao XIE; Wen WEN; Qinqin TANG; Yunlong LIU; Gaochang XIE; Tao HUANG (Tongxin xuebao)
The introduction of mobile edge computing (MEC) technology in rail transit which has the characteristics of complex environment, high densities of passengers, and high-speed mobility can meet the low latency, mobility, and massive connection requirements of rail transit.However, MEC not only improves the performance of rail transit communication network but also brings security challenges.Firstly, an overview of rail transit communication network and MEC was given.Then the value of introducing MEC into rail transit and the architecture of rail transit edge computing network were discussed.After that, the security threats faced by rail transit edge computing network was analyzed and protection scheme was proposed.Finally, some open questions were proposed, which was expected to provide ideas for future research.